EFEKTIVITAS PENGAWASAN KEUANGAN DAERAH PADA PEMERINTAH KOTA MAKASSAR - Nurfaidah Nurfaidah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
This study aims to determine the effectiveness of Regional Financial Supervision Performed by the Inspectorate of Makassar City. The method of analysis used is qualitative descriptive analysis method, used to explain the local financial supervision by the Inspectorate of Makassar City and Effectiveness Analysis method, used to determine the effectiveness of local financial supervision by the Inspectorate Makassar City, by using the ratio of the ratio between the realization of supervision with the supervision plan set by multiplied by 100%, in order to determine the level of effectiveness (results) achieved to achieve the goal. The results showed that the supervision undertaken by Inspektorak Makassar has been running in accordance with the standards has been set or is already effective.